Unravelling the role of iron and manganese oxides in colouring Late Antique glass by micro-XANES and micro-XRF spectroscopies - Gherardi, Francesca; Hole, Clément; Campbell, Ewan; Cotte, Marine; Tyson, Rachel; Paynter, Sarah (JPhys photonics, 2024)
This research aims to understand colouring technologies in 5th–7th centuries glass imported to Atlantic Britain by correlating the iron (Fe) and manganese (Mn) ratios and oxidation states with colour. Despite having a similar matrix chemical composition and concentrations of Fe and Mn oxides, these vessels display different colours (from green to yellow/amber, sometimes with purple streaks). Colour changes can be induced by controlling the reduction-oxidation reactions that occur during glass production, which are influenced by the raw materials, furnace and melt atmosphere, and recycling. To evaluate these parameters, reference glasses were prepared, following the composition of Late Antique archaeological glass recovered from Tintagel (UK) and Whithorn (UK). A corpus of archaeological and experimental glass samples was analysed using bulk Fe and Mn K-edge x-ray absorption near edge structure (XANES) spectroscopy, micro-XANES and micro x-ray fluorescence ( μ -XRF) at beamline ID21, at the European Synchrotron Radiation Facility. Fe and Mn XANES spectra of the archaeological glass indicate that Fe and Mn are in a similar oxidation state in all the yellow samples, predominantly Fe 3+ and Mn 2+ . No detectable difference in Mn and Fe oxidation state occurs in the purple streaks compared to the yellow glass bulk but μ -XRF maps of the distribution of Fe and Mn show that Mn is more concentrated in the purple streaks. This indicates that the purple colour of the streaks is mainly due to a higher Mn/Fe ratio and persistence of more oxidised manganese in the purple areas, even though it is difficult to detect. Many archaeological fragments appear pale green in transmitted light but amber in reflected light. XANES studies detected the presence of surface layers where manganese is more oxidised. This layer is believed to scatter transmitted and reflected light differently and might be responsible for the optical features of the archaeological glass.